An Analysis of Civic Education Students’ Perception toward Their Needs in Learning English for Specific Purpose in University Of Mataram - Andri Okta Firmansyah; Muhammad Fadjri; H. Lalu Nurtaat; Amrullah Amrullah (Jurnal Ilmiah Profesi Pendidikan, 2023)
In Indonesia, English is now a compulsory subject in undergraduate programs, regardless of whether students are enrolled in Non-English or English Departments. Non-English departments, including those in tourism, law, economics, pharmacy, and other fields, require English as well. The way English is taught in the civic department, for example, varies from how it is taught in the economics department. The language items and sub-skills necessary for the civic department differ from those required in the economics department. This study, aim to examine civic students’ necessities, lacks, and wants in learning English & Analyze civic students’ perception toward the ESP program in fulfilling their lacks and wants in learning English. This research descriptive qualitative researcher. The population of this study was 160 of civic education students ‘who were studying in University Of Mataram academic year 2021-2022. The number of samples used was 30 students who were taken using purposive sampling techniques. In gathering the data, this study used a questionnaire and an interview. The questionnaire consists of questions related to demographic information, necessities, wants, lacks, and perceptions toward the English program in fulfilling the students' wants. Meanwhile, a semi-structured interview was used to strengthen the data from the questionnaire. The research data show that civic education students needed English to pass the TOFL exam, which 43.3% did, followed by learning it for future careers, which accounted for 40% of their responses. Furthermore, most of the students wanted to be able to master vocabulary in English related to citizenship studies, listen to speeches and other spoken resources in English, write civic documents in English, and be able to read English civic documents at the end of the English course. Furthermore, it was discovered that the majority of them lacked speaking and listening skills. In terms of student perception, it was discovered that civic education students perceived the English program as fulfilling their wants because they were provided with learning techniques to satisfy their wants and lacks.